A Novel Fractal Coding Method Based on M-J Sets - Sun, Yuanyuan; Xu, Rudan; Chen, Lina; Kong, Ruiqing; Hu, Xiaopeng (PloS one, 2014)
In this paper, we present a novel fractal coding method with the block classification scheme based on a shared domain block pool. In our method, the domain block pool is called dictionary and is constructed from fractal Julia sets. The image is encoded by searching the best matching domain block with the same BTC (Block Truncation Coding) value in the dictionary. The experimental results show that the scheme is competent both in encoding speed and in reconstruction quality. Particularly for large images, the proposed method can avoid excessive growth of the computational complexity compared with the traditional fractal coding algorithm.